The Paramount Role of Translation in Modern Opera Productions - Ożarowska, Aleksandra (Text Matters: A Journal of Literature, Theory and Culture, 2017)
Opera is undoubtedly a particularly high and traditional genre of art, but recently there have been numerous attempts at breaking this stereotype and presenting opera in a contemporary light. The most popular way of achieving this aim is either staging modernized opera productions, i.e. transferring their plot from their traditional setting to the here and now, or considerably changing their interpretation. Staging modernized productions involves, first of all, the issue of stage design, and an alteration in the traditional interpretation is mostly created by acting, but nowadays it is also the translation shown in the form of surtitles that creates the significance of operatic productions.